The Housing Market Impacts of Shale Gas Development - Muehlenbachs, Lucija; Spiller, Elisheba; Timmins, Christopher (American Economic Review, 2015)
Using data from Pennsylvania and an array of empirical techniques to control for confounding factors, we recover hedonic estimates of property value impacts from nearby shale gas development that vary with water source, well productivity, and visibility. Results indicate large negative impacts on nearby groundwater-dependent homes, while piped-water-dependent homes exhibit smaller positive impacts, suggesting benefits from lease payments. Results have implications for the debate over regulation of shale gas development. (JEL L71, Q35, Q53, R31)